The factory site selection task solution by multiple criteria decision method KEMIRA - Krylovas, Aleksandras; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2015)
In the article waste processing plant siting task is solved by MCDM method KEMIRA. This method is appropriate for comparing few alternatives using criteria of two (or more) of heterogeneous types. Kemeny median is applied for ranking the alternatives. Weights determining task is solved by solving optimization problem. The results are compared with the results obtained for the same task using AHP and ARAS-F methods.
Keywords: multiple criteria decision making; KEMIRA method